2020
DOI: 10.32322/jhsm.720938
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices about pharmacovigilance and adverse drug reactions among dental research assistants in a Turkish hospital: a cross-sectional study

Abstract: This work is licensed under a Creative Commons Attribution 4.0 International License. Knowledge, attitude and practices about pharmacovigilance and adverse drug reactions among dental research assistants in a Turkish hospital: a cross-sectional study Bir Türk hastanesindeki diş araştırma asistanları arasında farmakovijilans ve advers ilaç reaksiyonları hakkında bilgi, tutum ve uygulamalar: kesitsel bir çalışma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 14 publications
5
7
0
Order By: Relevance
“…This difference may be due to the type of questions used in the studies. 8 Nevertheless, 17.5% of the participants mixed the terms "ADR" and "side effect" in this study, which was similar to a recent study among HPs that included dentists (22.7%). 14 Recent Turkish studies demonstrated that most dentists had never seen or experienced any ADR before.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This difference may be due to the type of questions used in the studies. 8 Nevertheless, 17.5% of the participants mixed the terms "ADR" and "side effect" in this study, which was similar to a recent study among HPs that included dentists (22.7%). 14 Recent Turkish studies demonstrated that most dentists had never seen or experienced any ADR before.…”
Section: Discussionsupporting
confidence: 89%
“…14 Recent Turkish studies demonstrated that most dentists had never seen or experienced any ADR before. 8,21 In contrast to these studies, the rate of dentists who had never diagnosed an ADR was low (34.7%) in this study, which was similar to that in Khan et al's 17 study (34.4%). Furthermore, 52.5% of the dentists, most of whom were SDs and participants with >12 years of experience, had encountered an oral mucosal ADR during their professional lives in this study.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations